Immigration as a democratic challenge : citizenship and inclusion in Germany and the United States - Rubio-Marín, Ruth (Cambridge University Press, 2000)
Immigration raises a number of important moral issues regarding access to the rights and privileges of citizenship. Examining the constitutional practice of Germany and the United States, this book argues that immigration policy in most Western democracies is unjust and undemocratic, and that policy should be far more inclusive.